(untitled) (Northern International Medical College Journal, 2018)
Background : Poor genital hygiene has been responsible for high prevalence of excessive vaginal discharge. Leucorrhoea is the clinical evidence of infection and can be treated satisfactorily whenever diagnosed. Occurrence of various cervical epithelial lesion associated with discharge can be easily prevented if detected early. Majority of the patients with various cervical epithelial lesion attending in the hospital present with varying degree of vaginal discharge and cytological cellular aberrations in the cervical epithelium. Objective : The aim of the present study is to observe the various patterns of cervical epithelial lesions in cytopathology and associated infections in patients with Leucorrhoea. Methodology : This observational study was done over a period of ten months in Popular Medical college hospitals of Bangladesh. A total of 230 cases were included in the study with women of age range 15-45 years, complaining of leucorrhoea. After a thorough vaginal examination Pap smears were taken and immediately fixed in absolute alcohol and stained according to the papanicolaous technique. The cytopathological changes observed in the cervical smears were graded according to the Bethesda system for reporting cervical cytology. Results : Out of 230 cases the cytological patterns were found Normal in 4 (1.7%), Inflammatory 204 (88.3%), Low grade squamous intraepithelial (LSIL)10 (4.8%), High grade squamous intraepithelial (HSIL) 6(2.6%), Atypical squamous cells of undetermined significance (ASCUS) 6 (2.6%) and the distribution of different types of pathogens detected were Trichomonas 33 (70.62%), Candida albicans 19 (40.66%). Conclusion : In this study significant numbers of Leucorrhoea patients were detected with cervical squamous intraepithelial lesions (SIL) in which LSIL (Low grade squamous intraepithelial) was higher. Associated infections were Trichomonas and Candida albicans. Therefore cytological screening for early detection of cervical squamous intraepithelial lesion is essential routine medical examination for Leucorrhoea patients in gynaecological practice. Northern International Medical College Journal Vol.9(1) July 2017: 252-254